The Effect of Project Based Learning Model Assisted by Short Film on the Short Story Writing Skills - Balqis Sabrita; Ermawati Arief; Dadi Satria; Nofrahadi (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe: 1) the pre-test results of short story writing skills for the control and treatment groups; 2) the post-test results of short story writing skills in the control and treatment groups; 3) the effect of the project-based learning model assisted by film media on short story writing skills. This study used a quasi-experimental design with a nonequivalent control group design. The study population was all 235 eighth-grade students of SMP Negeri 5 Padang Panjang in the 2025/2026 academic year. The sample was determined through a purposive sampling technique, namely class VIII.3 as the experimental class and VIII.2 as the control class, with 32 students each. Data on short story writing skills were collected using a performance test that was compiled objectively and systematically. Data on short story writing skills were analyzed using descriptive statistics, namely the mean and percentage. Data on the effect of project-based learning assisted by film media on short story writing skills were analyzed using nonparametric inferential statistics, namely the Mann-Whitney test. The results of the study: 1) the mean pretest of short story writing skills of the control group and the treatment group were each categorized as sufficient; 2) the mean posttest of short story writing skills of the control group was categorized as good but the mean posttest of the experimental group was categorized as very good; 3) the project-based learning model assisted by film media was very influential in learning short story writing skills.